2022
DOI: 10.1021/jacs.2c00581
|View full text |Cite
|
Sign up to set email alerts
|

Anionic Species Regulate Chemical Storage in Nanometer Vesicles and Amperometrically Detected Exocytotic Dynamics

Abstract: Hofmeister effects have often been ignored in living organisms, although they affect the activity and functions of biological molecules. Herein, amperometry has been applied to show that the vesicular content, dynamics of exocytosis and vesicles opening, depend on the anionic species treatment. Compared to 100 μM Cl − treated chromaffin cells, a similar number of catecholamine molecules is released after chaotropic anions (ClO 4 − and SCN − ) treatment, even though the vesicular catecholamine content significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 52 publications
0
13
0
Order By: Relevance
“…Recently, the molecule count and rupture kinetics have been correlated with vesicular size by using open carbon nanopipettes, [109] allowing simultaneous quantification of the nanovesicle size and catecholamine content by combining resistive pulses in a nanopipette and VIEC [110] . It has been observed that the vesicle opening measured by IVIEC can be regulated differentially by ions along the Hofmeister series [91] . This then permitted simultaneous counting of molecules in the native halo and dense core of nanovesicles by using the Hofmeister effect to regulate the dynamics of vesicle opening [111] .…”
Section: Hofmeister Effects On Vesicle Openingmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, the molecule count and rupture kinetics have been correlated with vesicular size by using open carbon nanopipettes, [109] allowing simultaneous quantification of the nanovesicle size and catecholamine content by combining resistive pulses in a nanopipette and VIEC [110] . It has been observed that the vesicle opening measured by IVIEC can be regulated differentially by ions along the Hofmeister series [91] . This then permitted simultaneous counting of molecules in the native halo and dense core of nanovesicles by using the Hofmeister effect to regulate the dynamics of vesicle opening [111] .…”
Section: Hofmeister Effects On Vesicle Openingmentioning
confidence: 99%
“…Thus, SCA was applied to study the effects of different anions at micromolar level on the exocytosis of chromaffin cells triggered by 30 mM KCl solution following a more chronic exposure to anions in the Hofmeister series. [91] Chromaffin cells were treated with 100 μM KX (X À : Cl À , Br À , NO 3 À , ClO 4 À , SCN À ) for 3 h before applying amperometric methods to measure stimulated release. Quantifying catecholamine release during exocytosis after the longer treatment with different anions shows that it remains nearly the same (i. e., 1 187 000 � 35 000 molecules for Cl À , 1 215 000 � 40 000 molecules for ClO 4 À , and 1 208 000 � 48 000 molecules for SCN À ), which is consistent with the effects of zinc on the amount of release.…”
Section: Cellular Exocytosismentioning
confidence: 99%
See 1 more Smart Citation
“…Positron emission tomography has been used to image the free-moving mouse brain but is still limited by low spatial resolution. Advances in electrochemical microelectrode technology have allowed researchers to monitor changes in a wide range of chemical signals with excellent spatial and temporal resolutions. Wightman et al pioneered a fast scan cyclic voltammetry (FSCV) technique to monitor electroactive substances such as dopamine in vivo using a direct redox reaction with high temporal resolution. , To further improve the selectivity and accuracy of thw in vivo determination, our group proposed a rational tailoring strategy for functionalized electrode surfaces to promote the electron transfer properties of the modified superoxide dismutase (SOD) and cytochrome c (Cyt c), which enabled us to develop new methods to detect the superoxide anion (O 2 •– ) and H 2 O 2 in vivo. , On the other hand, a variety of highly selective sensors were developed by assembling these recognition molecules on the nanostructured surface of the electrodes. In addition, differences in experimental environments and probe concentrations often lead to measurement errors. To establish a quantitative method for in vivo measurements, we designed ratiometric analytical strategies with an inner reference to provide built-in corrections to quantify Cu 2+ and l -cysteine in the living brain. , These advances were summarized in our previous papers and reviews. …”
Section: Introductionmentioning
confidence: 99%
“…Anionic species play a crucial role in chemical, biological, and environmental events, and more and more research groups are focusing on identifying anions, which are rapidly developing into a new area of interest in supramolecular chemistry. Potassium ferricyanide (K 3 [Fe­(CN) 6 ]) was discovered in 1822; the central atom of this substance is iron ion (Fe 3+ ), the ligand is cyanide ion (CN – ), and it is very stable as a solid at room temperature. Potassium cyanide can be produced by burning.…”
Section: Introductionmentioning
confidence: 99%